Pengembangan Sistem Informasi Manajemen Rapat berbasis Web (Studi Kasus : PT Sea Mobile Indonesia) - Safitri Herdian Rachmawati; Issa Arwani; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
PT Sea Mobile Indonesia is a private company engaged in the wholesale trade for fees or contracts which includes the business of agents who receive intermediaries, commissions, auctions, and other wholesalers. Meeting activities are one of the communication processes that are often carried out to negotiate or resolve problems that require a good management process. However, at PT Sea Mobile Indonesia meeting activities still experienced several obstacles such as uneven distribution of meeting information and the attendance and recapitulation processes still using the manual method. Based on these problems, a solution was found, namely the development of a web-based meeting management information system. This development uses the waterfall method with an MVC architecture that uses the Laravel framework and MySQL database. The system is integrated with WhatsApp where WABLAS is the WhatsApp gateway service. Then system tested by using validation, compatibility, and usability testing. Validation testing using the black box method with a success rate of 100% valid. While the results of the compatibility test are compatible, showing that the system can run well on various web browsers and the percentage of usability testing is 82%, meaning the system is in a very feasible category. While the results of the analysis of the efficiency aspect obtained a value of 3.97, meaning that the system has provided satisfaction to the user in finding the information sought and the ease of navigation of the meeting management information system menu.